The dinoflagellate cyst genera Achomosphaera Evitt 1963 and Spiniferites Mantell 1850 in Pliocene to modern sediments: a summary of round table discussions. (20th December 2018) - Mertens, Kenneth Neil; Van Nieuwenhove, Nicolas; Gurdebeke, Pieter R.; Aydin, Hilal; Bogus, Kara; Bringué, Manuel; Dale, Barrie; De Schepper, Stijn; de Vernal, Anne; Ellegaard, Marianne; Grothe, Arjen; Gu, Haifeng; et al.
Abstract: We present a summary of two round-table discussions held during two subsequent workshops in Montreal (Canada) on 16 April 2014 and Ostend (Belgium) on 8 July 2015. Five species of the genus Achomosphaera Evitt1963 and 33 of the genus Spiniferites Mantell 1850 emend. Sarjeant1970 occuring in Pliocene to modern sediments are listed and briefly described along with remarks made by workshop participants. In addition, several holotypes and topotypes are reillustrated. Three species previously assigned to Spiniferites are here considered/accepted as belonging to other genera: Impagidinium inaequalis (Wall and Dale in Wall et al.1973 ) Londeix et al.2009, Spiniferites ? rubinus (Rossignol1962 ex Rossignol1964 ) Sarjeant1970, and Thalassiphora balcanica Balteş 1971. This summary forms the basis for a set of papers that follows, where points raised during the workshops are explored in greater detail.